Membangun Partisipasi Pemda Aceh Utara pada Penyusunan Qanun Tentang Pengelolaan Aset Daerah: Building North Aceh Regional Government Participation in Preparation Qanun Concerning Regional Asset Management - Mukhlis, Mukhlis; Faisal, Faisal; Muammar, Muammar; Tasyukur, Tasyukur; Gani, Fauzi A. (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The qanun design process refers to Aceh Qanun Number 5 of 2011 concerning Procedures for Forming Qanuns. Article 22 of the Qanun states that the community provides verbal/written input in forming the Qanun. North Aceh Regional Government participation and community input on the draft revision of regional property management qanun was carried out through Focus Group Discussions (FGD). Existing Qanuns related to Regional Property must be adjusted to Government Regulation 28 of 2020 concerning the Management of State or Regional Property. This activity was carried out as a Focus Group Discussion (FGD) with stages of material delivery, question and answer, and interviews. This activity aims to obtain input on the draft qanun regarding managing goods owned by the North Aceh Regency area. Participants in this activity are government elements, community leaders, academics, and NGOs. After the FGD was carried out, the draft qanun was revised based on input to perfect the raqan, including the need for perfect administration of regional property from the planning stage to destroying assets belonging to the North Aceh Regency region. Apart from that, it is necessary to maintain and secure regional property so that the value and quality of assets are always maintained. Then, a good understanding is needed for regional property managers so they can carry out management properly and correctly by the mechanisms provided by law.